HUBUNGAN VISUS DENGAN RISIKO JATUH PADA LANSIA DI KELURAHAN BACIRO YOGYAKARTA - Amadea Rigenastiti; The Maria Meiwati Widagdo; Yanti Ivana Suryanto (Berkala Ilmiah Kedokteran Duta Wacana, 2018)
Background: The aging process causes changes of physiological and psychosocial functions. The percentage of older people population in Yogyakarta Province in 2015 was 13,49%, the highest in Indonesia. The increased number of older people is followed by the increased number of problems in older people. One of the most common problems of older people is falls. Risk of falls consists of intrinsic and extrinsic factors. Visual acuity is a part of the intrinsic factor of risk of falls in the older people. Objective: To find out the correlation between visual acuity and the risk of falls of older people in Baciro Village Yogyakarta. Methods: The research method was observational-analytic with cross sectional design. Researchers took samples in Baciro Village Yogyakarta. The inclusion criteria was people aged ≥60 years old. The exclusion criteria were older people who were illiterate and had neuromotor limitations in lower extremity.The data was collected by checking the visual acuity of the older people with Snellen chart. Falls Efficacy Scale International (FES-I) questionnaire was used to determine the risk of falling. Results: Ninety-seven older people participated in this research.The results of bivariate analysis used Spearman correlation test showed that there was no correlation between the better eye visual acuity and the risk of falls in the older people (FES-I) (r = 0.190 and p = 0.063) and there was a significant correlation between the worse eye visual acuity and the risk of falls in the older people (r = 0.240 and p = 0.018). Conclution: 1) There is no correlation between the better eye visual acuity and the risk of falls in the older people. 2) There is a correlation between the worse eye visual acuity and the risk of falls in the older people. Keywords: Visual acuity, Risk of Falls, FES-I